Microhabitat distributions and species interactions of ectoparasites on the gills of cichlid fish in Lake Victoria, Tanzania - Gobbin, Tiziana P; Vanhove, Maarten P M; Seehausen, Ole; Maan, Martine E (International journal for parasitology, 2021)
Heterogeneous exposure to parasites may contribute to host species differentiation. Hosts often harbour multiple parasite species which may interact and thus modify each other's effects on host fitness. Antagonistic or synergistic interactions between parasites may be detectable as niche segregation within hosts. Consequently, the within-host distribution of different parasite taxa may constitute an important axis of infection variation among host populations and species. We investigated the microhabitat distributions and species interactions of gill parasites (four genera) infecting 14 sympatric cichlid species in Lake Victoria, Tanzania. We found that the two most abundant ectoparasite genera (the monogenean Cichlidogyrus spp. and the copepod Lamproglena monodi) were non-randomly distributed across the host gills and their spatial distribution differed between host species. This may indicate microhabitat selection by the parasites and cryptic differences in the host-parasite interaction among host species. Relationships among ectoparasite genera were synergistic: the abundances of Cichlidogyrus spp. and the copepods L. monodi and Ergasilus lamellifer tended to be positively correlated. In contrast, relationships among morphospecies of Cichlidogyrus were antagonistic: the abundances of morphospecies were negatively correlated. Together with niche overlap, this suggests competition among morphospecies of Cichlidogyrus. We also assessed the reproductive activity of the copepod species (the proportion of individuals carrying egg clutches), as it may be affected by the presence of other parasites and provide another indicator of the species specificity of the host-parasite relationship. Copepod reproductive activity did not differ between host species and was not associated with the presence or abundance of other parasites, suggesting that these are generalist parasites, thriving in all cichlid species examined from Lake Victoria.
Keywords: Cichlidae; Gills; žábry; Parasites; Copepoda; Niche selection; Host–parasite interaction; jezera; Cichlids; cichlidy; paraziti; zvířata; Tanzanie; Humans; Monogenea; Parasite–parasite interaction; nemoci ryb; Host-Parasite Interactions; Lakes; interakce hostitele a parazita; Fish Diseases; Tanzania; lidé; Animals